Persepsi Ibu Bapa Terhadap Penggunaan Telefon Mudah Alih dalam Kalangan Kanak-Kanak Di Parit Raja , Johor - Ngadiman, Yunos; Kamal, Amanina (Research in Management of Technology and Business, 2021)
Today, in the era of modernization of technology, mobile telephone tools among these children are growing rapidly in Malaysia and have become a tradition of human everyday life. It has also brought various parental perceptions on the use of mobile phones among children. In order to address this issue, this study aims to identify parental perceptions on the use of mobile phones from aspects of purchasing, use and telephone ownership among children and determine the most influential aspects of parental perceptions on the use of mobile phones. Quantitative methods are used to collect data through structured questionnaires from 364 parents in Parit Raja, Johor. However, from 364 respondents but only 264 questions have been answered in the question of this study. The data obtained were analyzed using the Statistical Package for Social Science (SPSS) software version 24 to get the percentage value, mean and standard deviation. The main importance of this study is to identify the effect of the effectiveness of mobile phones among children. Based on this study, the level of mean analysis in positive items affects parental perceptions. Additionally, Spearman’s correlation coefficient test shows that ownership, use and purchase is seen positively with parental perceptions. In conclusion, every parent and all parties should take note of and monitor the use of this mobile phone among childrens so that its does not bring harm using.